Comparison of palatal dimension in children with obstructive and habitual mouth breathing - Soni Kottayi; Sneha Pramod; Faizal C. Peedikayil; Athira Aravind; Aswathi Sreedharan; Athul Ramesh (Journal of Indian Society of Pedodontics and Preventive Dentistry)
Background: Prolonged mouth breathing (MB) can produce muscular and postural alterations which in turn can cause changes on the morphology, position, and growth direction of the jaws. Therefore, a study was planned to compare the palatal dimension in obstructive and habitual mouth breathers with that of nasal breathers. Materials and Methods: The total sample of 75 subjects is divided into three groups with 25 patients in each group – Group A: patients with obstructive MB habit, Group B: patients with habitual MB habit, and Group C: patients with nasal breathing (control group). A maxillary cast model was prepared from these patients and the following parameters were determined using digital vernier calipers – canine distance, canine depth, palatal width, palatal height, and palatal index. One-way ANOVA with post hoc test was used to compare between the groups. P < 0.05 was considered statistically significant. Results: The comparison of hard palate dimensions observed in nasal breathers, obstructive and habitual mouth breathers showed differences regarding the distance and depth of first molars. The lowest palatal width was observed in obstructive mouth breathers with a mean width of 33.25 (3.42). 56% of obstructive mouth breathers had high palatal depth compared to control (36%) and habitual mouth breathers (28%) groups. Conclusion: Obstructive mouth breathers exhibited the lowest palatal width, accompanied by the highest palatal height and depth when compared to habitual mouth breathers and nasal breathers. It is also evident that obstructive mouth breathers presented a deeper hard palate when compared to habitual mouth breathers and nasal breathers.